The calculating entrepreneur — The role of economic calculation in supporting alertness and creative destruction - Eduard Braun; Florian Follert (Managerial and Decision Economics, 2024)
Abstract We integrate the issue of economic calculation into the theory of the entrepreneur. In doing so, we fill a gap in the literature by demonstrating that retrospective economic calculation, i.e., financial accounting, dovetails with Kirzner's theory of the alert entrepreneur and that prospective calculation, i.e., the appraisal of investment objects, supports innovational activities by entrepreneurs and therefore facilitates creative destruction as emphasized by Schumpeter. Our integrative conceptualization of the calculating entrepreneur can lead to a better understanding of the role of economic calculation in the economy, thereby bringing theoretical economics and business administration closer together.
Keywords: 330